Sosialisasi TRIPLE P (Pedoman Gizi Seimbang, PHBS dan Penerapan Isi Piringku) pada Siswa SDN 213 Gresik - Nandasari, Anggy Dwipa; Aidilfi Akbar, Dimas Arendra; Widya Putra, Bima Arya; Miladiya, Feby Ayu; Nurdinata, Sandra Maulida; Afianti Diah Anjelia; Septyanengrum, Rita; Intan Oktariza Nuraulya Putri; Andini Devi Rizkiyah; Nuris Lutfika; Syiddatul Budury; Ersalina Nidianti (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
The Indonesian nation as a developing country faces many nutritional problems, especially in children. If nutritional needs are not met properly, it can cause children to experience growth and development problems that affect them until they become adults. This activity was held at SDN 213 Gresik which targeted students from grades 1-3. In carrying out the activities, the team used socialization and educational methods in the form of delivering material, holding games and coloring competitions, as well as demonstrations. The results of this KKN activity students are able to understand and know the guidelines for balanced nutrition, apply how to wash hands properly in the context of Clean and Healthy Behavior (PHBS) and Application of My Plate Contents as a substitute for the slogan 4 healthy 5 perfect. In the Socialization of Balanced Nutrition Guidelines, PHBS and Application of My Plate Contents to Students of SDN 213 Gresik Grades 1-3, almost all participants actively and enthusiastically took part in the activity by paying serious attention to the material provided and also actively asking questions when someone wanted to know more.